Empreendedorismo digital no setor bancário brasileiro: uma análise de instituições bancárias tradicionais com o surgimento das fintechs - Pinto, Alexandre Rodrigues (2020)
Due to their importance in society, there is a view that traditional Brazilian banking institutions do not have the need to worry about the market in which they belong, as they perceive that they do not face financial or competition difficulties. However, they also need to remain attentive to market movements and innovations, so as not to lose their prominent positions in the sector. This research seeks to analyze the changes occurred in traditional Brazilian banking institutions towards digital entrepreneurship, due to the emergence of fintechs. The research is of a qualitative nature, with analysis of multiple cases in the three largest Brazilian banking institutions in terms of managed assets, equity and profit, being, respectively, Itaú Unibanco, Bradesco and Banco do Brasil. The data were collected through interviews and secondary data analysis. Interviews were conducted with 30 management-level employees, with a script developed from a conceptual model observing the main aspects of digital entrepreneurship highlighted in the literature. Through the interpretation of the respondents' reports and the analysis of the secondary data, it was evaluated, from the perspective of institutional isomorphism, the factors that had the greatest influence on the advancement of digital entrepreneurship since the emergence of fintechs. Through the results, the study adds theoretical contributions expanding the corresponding literature to this field of study and presents a theoretical framework of resources and factors of digital entrepreneurship, which was consolidated in the literature and evaluated in practice. In institutional theory, the presence of institutional forces in traditional banking institutions was analyzed, identifying coercive, mimetic and normative movements. In terms of practical contributions, the study allows institutions to understand how fintechs influence the advancement of digital entrepreneurship in the banking sector, in addition to excerpts extracted from the interviews, which can be understood as experience and a source of learning for professionals in the sector.